Failure of care in state care: in-care abuse and postcare homelessness - Thoresen, Stian; Liddiard, Mark (Australian Academic Press, 2011)
This paper reviews initial findings from an AHURI (Australian Housing and Urban Research Institute)-funded research project examining housing outcomes amongst Australian young people who have been in state out-of-home care. Our findings suggest a linkage between incidents of in-care abuse and poor postcare housing outcomes amongst our research participants, including primary homelessness. Not attending school when leaving care was also highly associated with having experienced in-care abuse. The authors postulate that adverse in-care experiences may have contributed to poor postcare housing outcomes amongst the research participants and this paper raises a number of specific concerns related to neglect, abuse and assault whilst in care. It is also argued that support in the transition from care needs to be strengthened to mitigate poor postcare outcomes, as does accountability for in-care adversities.